2010
DOI: 10.1118/1.3469169
|View full text |Cite
|
Sign up to set email alerts
|

TU‐A‐204B‐02: On the Potential of CBCT for Range Verification in Proton Therapy

Abstract: Purpose: We have investigated the potential use of cone beam CT (CBCT) for beam range verifications in proton therapy treatment, in addition to its primary role in geometric targeting. Specifically, we studied the intrinsic imaging variability of a CBCT and its effect on the water equivalent path length (WEPL) calculations, in the context of daily beam range verification/correction required for a recently proposed method of treating prostate using anterior fields. The current approach uses only lateral fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…12 It may however be possible to obtain accurate stopping power estimates by performing deformable image registration () between the planning CT (pCT) and CBCT. This has been explored by several groups in the context of adaptive photon therapy for photon dose recalculation and automatic contour propagation.…”
Section: Introductionmentioning
confidence: 99%
“…12 It may however be possible to obtain accurate stopping power estimates by performing deformable image registration () between the planning CT (pCT) and CBCT. This has been explored by several groups in the context of adaptive photon therapy for photon dose recalculation and automatic contour propagation.…”
Section: Introductionmentioning
confidence: 99%
“…While for photon therapy it may be possible to perform CT number to electron density calibration and achieve acceptable dose calculation accuracy for uncorrected CBCT images (Yang et al 2007), this has not been demonstrated for protons where CBCT intensity correction to match CT image intensities is most likely required. Preliminary studies have investigated CT num-ber correction for CBCT images (Bentefour et al 2010). It may be possible to obtain accurate stopping power estimates by performing deformable image registration (DIR) between the planning CT and CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…question is, whether CBCT can be used also for tracking daily variations of the patient waterequivalent path length and, subsequently, could be used as tool for beam range check before proton therapy treatment? (3) Range uncertainty is one of the most difficult problems in particle therapy treatment. (4,5) Such uncertainty translates directly into potential undershooting or overshooting of the Bragg peak in the patient.…”
mentioning
confidence: 99%